2017
DOI: 10.1016/j.toxrep.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

In vivo immunoprotective role of Indigofera tinctoria and Scoparia dulcis aqueous extracts against chronic noise stress induced immune abnormalities in Wistar albino rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Plant diet plays a vital role in the physiological mechanisms of vertebrate and invertebrate and also improve immunity [ 45 , 46 ]. The quality and quantity of plant diet determine insect fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Plant diet plays a vital role in the physiological mechanisms of vertebrate and invertebrate and also improve immunity [ 45 , 46 ]. The quality and quantity of plant diet determine insect fitness.…”
Section: Discussionmentioning
confidence: 99%
“…AChE activity was determined by the addition of acetylcholine (0.02 ml), cell culture supernatant (0.02 ml), DTNB (0.1 ml) and phosphate buffer (3 ml) into the reaction tube. The final absorbance was measured at 410 nm ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers have found that the levels of immunoactive substances in the blood circulation, such as IgG and IgM ( 7 ), and of sIgA ( 9 , 22 ) in the local mucosa are decreased after prolonged noise exposure. The quantities and activity of immune cells such as T-lymphocytes ( 8 ), phagocytes ( 23 ), NK cells ( 16 ), and NKT cells ( 5 ) are reduced. In addition, the weights of immune organs/tissues such as the thymus ( 24 ), bone marrow ( 18 ), and spleen ( 14 ) are significantly reduced, and even the genetic material of cells ( 18 ) in bone marrow exhibits obvious adverse changes ( 4 ).…”
Section: Correlation Between Noise and The Immune Systemmentioning
confidence: 99%
“… Changes in the immune system after exposure to noise or music. Most components, including the internal ear ( 21 ), exocrine secretions ( 9 ), thymus ( 24 ), lymph nodes ( 14 ), spleen ( 14 ), digestive tract ( 17 ), marrow ( 18 ), immunoglobulins ( 7 , 8 , 16 ) and immune cells ( 5 , 7 , 10 , 11 ), are shown. …”
Section: Music and Immune Systemmentioning
confidence: 99%